Social and commercial entrepreneurship: same, different, or both? - Austin,James (2012)
Entrepreneurship has been the engine propelling much of the growth of the business sector as well as a driving force behind the rapid expansion of the social sector. This article offers a comparative analysis of commercial and social entrepreneurship using a prevailing analytical model from commercial entrepreneurship. The analysis highlights key similarities and differences between these two forms of entrepreneurship and presents a framework on how to approach the social entrepreneurial process more systematically and effectively. We explore the implications of this analysis of social entrepreneurship for both practitioners and researchers.